Implementation of Kafa'ah in Marriage: Comparative Study Between Customary Law and Islamic Law in Lendang Nangka Village, Masbagik District, East Lombok Regency - Mukhlis Ismail; Sainun; Rendra Khaldun; Mirwan (al-Afkar, Journal For Islamic Studies, 2025)
A harmonious marriage, apart from being based on compatibility and harmony, must also be based on aspects of equality or equality between the two partners. Not only in material aspects but also immaterial aspects such as lineage and nobility. Apart from that, the Sasak tribe also still adheres to patrilineal principles in the aspect of marriage. This is illustrated in the dichotomization of wedding processions between each level of society based on their background, such as menak and coral rows which are differentiated in the traditional procession. Because in every traditional process of merarik in the Sasak tribal community there are certain meanings in it, however, this has experienced shifts and changes in some villages in the Sasak tribe. Therefore, this merarik tradition deserves to be raised as a research subject, especially in its unique aspect, why the merarik tradition is used as a ritual that must be fulfilled. This research was carried out in Lendang Nangka village, Masbagik sub-district, East Lombok district. This research is also included in qualitative research, the research subjects of which consist of village heads, traditional heads, religious leaders and community leaders. The research results include: First, the process of attracting noble people and ordinary people before and after the marriage contract in Lendang Nangka Village is basically all almost the same, only it can be differentiated by the size of the existing aji krame. Then, most of the people of Lendang Nangka village have been able to accept changes, where the keskufu'an of the noble lineage can be compared with other material aspects.